2019
DOI: 10.1177/0361198118821343
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Traffic Volume on Pavement Macrotexture and Skid Resistance Long-Term Performance

Abstract: Pavement skid resistance is influenced by both pavement macrotexture and microtexture, with the two components providing the skid resistance properties required to assist in ensuring road safety. In addition to these factors the cumulative traffic along a pavement is a known determinant factor influencing pavement surface characteristics leading to deterioration. However, previous research efforts in this area have been evaluated based on laboratory experiments that have not proven to be easily extrapolated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Wu and Abadie simulated the wearing process with an accelerated polishing machine and measured MPD with a CTM, and the results indicated that the MPD values tended to remain constant under different polishing cycles [ 31 ]. Plati and Pomoni investigated the long-term field data of skid resistance and macro-texture and found that the MPD and grip number (GN) presented a contrary trend under traffic polish [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Abadie simulated the wearing process with an accelerated polishing machine and measured MPD with a CTM, and the results indicated that the MPD values tended to remain constant under different polishing cycles [ 31 ]. Plati and Pomoni investigated the long-term field data of skid resistance and macro-texture and found that the MPD and grip number (GN) presented a contrary trend under traffic polish [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As traffic load keeps on increasing, skid resistance decreases in the long term despite any interim increase [30]. Plati and Pomoni [72] investigated the long-term effect of traffic volume on skid resistance and macrotexture and observed that the traffic effect is not a constant factor during pavement service life. In one zone, it was observed that mean profile depth (MPD) and skid resistance exhibited a slow decrease with fluctuations during their evolution period, and in another zone of the test, which starts after a certain volume of cumulative traffic, mean profile depth presented an inverse trend with skid resistance: as MPD increases, skid resistance decreases.…”
Section: Effect Of Traffic Loadmentioning
confidence: 99%
“…Focusing on the vehicles' braking as a result of a vehicle-infrastructure interaction, friction between the tyre tread and pavement surface is the resistive force developed when a vehicle starts braking, prevented from rotating and instead skids along the pavement surface [13,14]. The frictional force between tyres and pavement is generally characterized by a dimensionless coefficient known as coefficient of friction (CoF), which is the ratio of the tangential force at the contact interface to the longitudinal force on the wheel as shown in Figure 1 and it is given by Equation (1) [15].…”
Section: Pavement Frictional Performancementioning
confidence: 99%